2020
DOI: 10.3390/su12083113
|View full text |Cite
|
Sign up to set email alerts
|

Young Pioneers, Vitality, and Commercial Gentrification in Mudan Street, Changchun, China

Abstract: The pioneers who started the gentrification process have contributed significantly to the activation of gentrified neighborhoods, but are often overlooked in top-down urban governance strategies. We studied the core participants, who were avant-garde café owners, in the initial stage of the commercial gentrification of Mudan Street in Changchun, China. By participatory observations and in-depth interviews, we closely investigated the statuses, behaviors, and preferences of the early gentrifiers, their contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In contrast, parking convenience did not seem to have a significant effect on visitor satisfaction with the area. The effect of walking safety on visitor satisfaction at a destination is inconsistent with the findings of previous studies [16]. It is believed that the result reflects the tendency of the millennial generation to prefer various new experiences in the place over the uniformity of well-maintained streets in general commercial districts to ensure pedestrian safety [29].…”
Section: Influence Of Instagram Usage On Visitor Satisfactionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, parking convenience did not seem to have a significant effect on visitor satisfaction with the area. The effect of walking safety on visitor satisfaction at a destination is inconsistent with the findings of previous studies [16]. It is believed that the result reflects the tendency of the millennial generation to prefer various new experiences in the place over the uniformity of well-maintained streets in general commercial districts to ensure pedestrian safety [29].…”
Section: Influence Of Instagram Usage On Visitor Satisfactionmentioning
confidence: 70%
“…Finally, the literature review also indicated that the characteristics of producers and consumers of the commercial district contribute to the formation of the "place properties" of the area. Furthermore, Shin and Choi (2010) stated that consumers' personal (private) properties within a commercial area also contribute to the unique properties of the location [15], and the role of young people is sometimes listed as a crucial factor, especially in the early formation stage of a commercial area [16]. In the process of creating and consuming commercial districts, the personality of young users is reflected in the shaping of a commercial district with unique properties [17].…”
Section: Influence Of "Place" Properties On Visitor Evaluationsmentioning
confidence: 99%
“…The humid continental climate with long, cold winters governs the regional biomes, which are represented by temperate conifer forests. After the reform and opening up of the country, Changchun gradually formed a service industry and commercial spaces, and it developed rapidly since the early 1980s [ 47 ]. In 2014, Changchun’s gross domestic product (GDP) reached 861.12 billion RMB Yuan, and its per capita disposable income reached 11335.85 RMB Yuan.…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%
“…There are other cases however where urban regeneration is sorely aimed at providing short-term physical solutions to induce gentrification [32]. Gentrification was born with urban regeneration in the 1960s in Western countries [30]. In respect of this, urban regeneration can be classified in a plethora of ways, however for this study, Turok's [26] classification of 'place', 'people' and 'business' seems applicable.…”
Section: Urban Regenerationmentioning
confidence: 99%